2014
DOI: 10.1111/jgs.12733
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention to Improve Internal Medicine Interns' Awareness of Hazards of Hospitalization in Acutely Ill Older Adults

Abstract: Hospitalized older adults are susceptible to complications termed "hazards of hospitalization" (HOH), which collectively result in poor patient outcomes. Previous research has shown that residents are not aware of their patients' risk factors for HOH. This study investigated the effect of an educational intervention to increase internal medicine interns' knowledge and self-efficacy of HOH and to improve their care of hospitalized older adults as measured by their documentation of HOH. Targeted learners were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38] The 14 studies are summarized in 27,29,[31][32][33][34]36 ; didactics 25,28,29 ; web-based 30 or electronic medical record modules 26 ; cues to action 38 ; decision support 27,37 or simulation combined with video and case discssion 38 ; grand rounds 29 ; interdisciplinary team meetings or rounding 29,32 ; geriatrics patient rounds 25,29,32 ; nursing home rounds 31 ; morning case report 28,29 ; independent study projects 29 ; formative feedback 35,38 ; and direct observation. 25 Learning outcomes were matched to Kirkpatrick levels 1 to 4. 19 As shown in TABLE 25,28,32,…”
Section: Study Selection and Descriptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38] The 14 studies are summarized in 27,29,[31][32][33][34]36 ; didactics 25,28,29 ; web-based 30 or electronic medical record modules 26 ; cues to action 38 ; decision support 27,37 or simulation combined with video and case discssion 38 ; grand rounds 29 ; interdisciplinary team meetings or rounding 29,32 ; geriatrics patient rounds 25,29,32 ; nursing home rounds 31 ; morning case report 28,29 ; independent study projects 29 ; formative feedback 35,38 ; and direct observation. 25 Learning outcomes were matched to Kirkpatrick levels 1 to 4. 19 As shown in TABLE 25,28,32,…”
Section: Study Selection and Descriptionsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][35][36][37][38] Of these, 10 reported statistically significant changes in knowledge and/or skills. 25,[29][30][31][32][33][35][36][37][38] Five studies reported behavioral changes in learners (Kirkpatrick Level 3), [25][26][27][28]30 and 3 of these changes were statistically significant. 25,26,30 No study reported changes in professional practice or benefits to patients (Kirkpatrick levels 4a and 4b).…”
Section: Learning Outcomesmentioning
confidence: 99%
See 3 more Smart Citations